Online learning motivation during Covid-19 pandemic: The role of learning environment, student self-efficacy and learner-instructor interaction - Shee, Mun Yong; Lip, Sam Thi (Universiti Utara Malaysia Press, 2022)
Purpose - Due to the COVID-19 pandemic, the Malaysian government declared a Movement Control Order (MCO) to prevent the spread of the virus. Educational institutions were forced to switch their pedagogy to online learning to complete the semester curriculum, catching academicians and students off-guard that resulted in makeshift online lesson delivery. Previous online learning motivation studies have neglected the impact of an unplanned or sudden transition to online learning during a pandemic on student motivation to learn. This study aims to examine location learning environment, learner-instructor interactions, and self-efficacy of students more succinctly on their learning motivation during an unplanned transition to online learning.